Spatial Interaction Regional Model for the Mexican Economy (SIRMME): A Special Case for Mexico City Metropolitan Area - Mendoza-González, Miguel Ángel; Valdivia-López, Marcos; Quintana-Romero, Luis (Journal of Reviews on Global Economics, 2016)
This paper analyzes empirically a macro model and a regional model to explain Mexico and Mexico City economies respectively. Typically, regional economic modeling considers either a top-down or bottom-up approach to model regional difference in economic growth. This paper shows results that explain regional difference in Mexico from the bottom-up through a special case that focuses on the spatial interaction between Mexico City -the main economic engine of Mexico- and the rest of the country during the period 2000-2010. Our results indicate that variables associated with human capital, internal migration, "creative class", micro-firms and spatial interaction among micro-regions were conditioning the differential growth between Mexico City and the whole country during the period 2000-2010. Likewise, we present econometric results of a typical macro model that explains economic growth in Mexico by different income effects on components of aggregate demand during the period 1993-2010. The purpose of both exercises is to motivate future research for the Mexican case to link macro components (such as export driven forces, MexicoÂ´s dependency to the USAÂ´s business cycle, loss of government spending, etc.) with their local counterparts such as agglomeration economies, human and creative capital stock, regional spillovers, natural resources, dynamic population, etc. to explain regional differential growth.